De militair tot zegen: Militaire tehuizen en de plaats van religie in de Nederlandse krijgsmacht, 1945-1950 - Jager, Koos-jan de (Trajecta, 2022)
This article studies the place of religion in the military welfare services of the Dutch Armed Forces during the Indonesian war of independence (1945-1950). During this war, the Dutch government deployed 200,000 soldiers in Indonesia. In the Netherlands debates arose on the immoral (sexual) behavior and religious decline of these soldiers. Military clubhouses were presented as a weapon in the fight against immorality. The Dutch army preferred ‘neutral’ clubhouses without a specific Protestant or Catholic identity but inclusive to everyone. However, Dutch churches and religious organizations successfully argued for clubhouses and welfare work based on a specific confessional tradition. Notwithstanding the discussions, the military clubhouses were of support for Dutch soldiers in Indonesia, whether it be explicit Christian or neutral institutions.